2020
DOI: 10.1177/1477750920946613
|View full text |Cite
|
Sign up to set email alerts
|

Refractory suffering at the end of life and the assisted dying debate: An interview study with palliative care nurses and doctors

Abstract: Background How often does refractory suffering, which is suffering due to symptoms that cannot be adequately controlled, occur at the end of life in modern palliative care? What are the causes of such refractory suffering? Should euthanasia be offered for refractory suffering at the end of life? We sought to shed light on these questions through interviews with palliative care specialists. Methods Semi-structured interviews with six nurses and six doctors working in palliative care in five Norwegian hospitals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The nurses in our study felt trapped in a situation that could not be resolved, making them feel vulnerable and powerless as they were unable to relieve suffering. This finding is comparable with that of the study by Gustad et al ( 2020 ) suggesting that nurses' lack of medical knowledge might lead to underdosing and, thereby, the unnecessary suffering of terminally ill patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The nurses in our study felt trapped in a situation that could not be resolved, making them feel vulnerable and powerless as they were unable to relieve suffering. This finding is comparable with that of the study by Gustad et al ( 2020 ) suggesting that nurses' lack of medical knowledge might lead to underdosing and, thereby, the unnecessary suffering of terminally ill patients.…”
Section: Discussionsupporting
confidence: 89%
“…In a review of the available literature undertaken in planning this study, it appeared that Norwegian nurses are invisible in the research literature and in public discussions about assisted dying. Information regarding their perceptions of requests for assisted dying is limited (Gustad et al, 2020 ; Hol et al, 2022 ). However, a recent survey among Norwegian nurses revealed that 58% of 205 responding nurses had received requests for assisted dying from terminally ill patients (Hol et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it would certainly have an impact on the euthanasia debate, as one of the main arguments against euthanasia is that effective symptom control can be achieved through DPS, thereby rendering euthanasia redundant at the end of life. 21 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, even where the removal of consciousness and/or the potential hastening of death are deemed to be ‘bad’ effects, this does not necessarily mean that TS should be reserved as an option of last resort. First, the process of exhausting other palliative care measures can take time and involve significant distress along the way 18. Second, the assessment of how much suffering (and over what period of time) counts as ‘refractory’ is inherently subjective and value based.…”
Section: Is Ets Morally Permissible?mentioning
confidence: 99%
“…First, the process of exhausting other palliative care measures can take time and involve significant distress along the way. 18 Second, the assessment of how much suffering (and over what period of time) counts as ‘refractory’ is inherently subjective and value based. Arguably, it is only the patient who can ultimately determine when suffering becomes intolerable.…”
Section: Is Ets Morally Permissible?mentioning
confidence: 99%